Improvement of the riding comfort for sentosa cable car cabin - 2 - Hwang, Benjamin Dewei. (2013)
Cable car systems are commonly found in ski resorts and mountainous area where the temperature is lower, therefore the basic design requirement of the cabin is to minimize the heat loss inside it. On the other hand, Singapore has a hot and humid climate. Using the same cable car system in Sentosa Singapore creates significant problems such as rising temperature and poor ventilation inside the cabin. Another constraint faced by the existing Cable Car System is the limited power available to the cabin. Since the cable supporting the cabin does not carry live power out of safety consideration, each cabin carries its own supercapacitor bank with limited capacity and would only be charged for a brief period when the cabin reaches and transverses through the station. The Sentosa Cable Car management had implemented some measures to tackle the issues, but the improvements were not effective. This project aims to provide a systematic study of the cable car design in Sentosa. It also aims to generate possible engineering solutions to solve the existing problems of the cabin, such as high temperatures and limited power storage capacity. Under such limitations, it becomes more challenging to come out with a cooling system for the cable car.